The breaking point - Bass, Jefferson (Bass, Jefferson. Body Farm novel., 2015)
Called in to identify some remains, Dr. Brockton finds his life plunged into chaos when his identification is called into question, a killer from his past returns, and his wife delivers some news that changes everything.